Surfaces of Revolution with Vanishing Curvature in Galilean 3-Space - Dede, M.; Ekici, C.; Goemans, W. (Журнал математической физики, анализа, геометрии, 2018)
In the paper, three types of surfaces of revolution in the Galilean 3- space are defined and studied. The construction of the well-known surface of revolution, defined as the trace of a planar curve rotated about an axis in the supporting plane of the curve, is given for the Galilean 3-space. Then we classify the surfaces of revolution with vanishing Gaussian curvature or vanishing mean curvature in the Galilean 3-space. У статтi визначено та дослiджено три типи поверхонь обертання у тривимiрному просторi Галiлея. Запропоновано конструкцiю поверхнi обертання у тривимiрному просторi Галiлея, визначено обертанням пласко криво навколо осi, що лежить у площинi криво . Класифiковано поверхнi обертання у тривимiрному просторi Галiлея з нульовою гауссовою кривиною та з нульовою середньою кривиною.